Evaluation of Ethiopian sorghum germplasm for resistance to anthracnose and performance for desirable agronomic traits - Chemeda Birhanu; Tesfaye Mengiste; Dagnachew Lule; Firew Mekbib; Zelalem Bekeko; Alemu Tirfessa; Pascal Okoye; Getachew Ayana; Gezahegn Girma; Habte Nida; Abera Takele (Agrosystems, Geosciences & Environment)
Abstract Anthracnose, caused by the fungus Colletotrichum sublineola, is an economically important disease of sorghum [(Sorghum bicolor (L.) Moench] in warm and humid regions of Ethiopia. Frequent screening for resistance sources and the development of resistant varieties is crucial for disease management, but achieving resistance has been challenging due to the high variability of the pathogen. A total of 358 Ethiopian sorghum landraces were evaluated to identify anthracnose resistance and other desirable agronomic traits under natural infestation in the field and inoculation of plants in the greenhouse. Field evaluations were conducted at Asosa, Bako, Jimma, and Haramaya in Ethiopia for two growing seasons. Greenhouse screening was performed at Purdue University using a mixture of five strains of C. sublineola. Under field conditions, area under disease progress curve was used to determine anthracnose disease severity. In addition, major agronomic traits such as panicle weight, panicle yield, grain yield, and thousand‐grain weight were recorded. Combined analysis of variance revealed highly significant (p < 0.01) differences among accessions, locations, and genotype‐by‐environment interactions for disease parameters and agronomic traits. We identified 71 accessions showing consistent resistance, developing disease severity levels between 12% and 30% across locations. The analysis of greenhouse multi‐strain screenings also revealed significant genetic variation with 33 accessions exhibiting resistant reactions without showing any disease symptoms. Overall, 55 accessions showed resistant reactions to anthracnose both under fields and greenhouse evaluations. The accessions with low anthracnose severity and high grain yield with desirable traits are valuable for future sorghum improvement programs.